Individual planning staff as an actor of GIS translation in the planning departments of Kuala Lumpur City Hall, Malaysia - Mohd. Hussain, Mohd. Ramzi; Johar, Foziah (International Journal of Technology Enhancements and Emerging Engineering Research, 2015)
The context of the planning organisation and the operation of political processes in the planning organisation have a substantial impact on the outcome of computerisation. However, there is also a need to consider the activities and characteristics of the individuals. The activity of individual planning staff can substantially affect the development and utilisation of computer-based systems. This paper explores the contributions of individual planning staff as an actor of GIS translation at the Department of Urban Planning (DUP) and the Master Plan Department (MPD) in Kuala Lumpur City Hall (KLCH) Malaysia. The paper employed a semi-structured interview to investigate role played by the individual planning staff and activities of the department. The findings demonstrate that the organisational context, people and technology has made a highly significant contribution in obtaining the resources necessary for the translation of computer-based information systems in the MPD and the DUP